Colo-colic intussusception secondary to colon lipoma: A case report - Kansoun, Alaa (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Intestinal intussusception is rare in adults and it is associated with lead points affecting the colon in around 17% of patients. Lipomas are very rare benign tumors which may act as lead points for intestinal intussusception. Indeed, the incidence of intestinal intussusception is much rare when caused by lipomas. CASE PRESENTATION: Our patient is a 29-year-old male, previously healthy and admitted for severe right lower quadrant abdominal pain of 2-day duration. Computed tomography (CT) scan of the abdomen and pelvis showed large mass of fat consistency containing colon structure. CLINICAL DISCUSSION: Urgent laparotomy was opted during which colo-colic intussusception was diagnosed and right hemicolectomy with primary ileocolic anastomosis was performed. Pathology report showed that intussusception was induced by a colon lipoma. Patient had an uneventful hospital stay and was discharged on post-operative day 5. CONCLUSION: Thus we recommend that colo-colic intussusception caused by lipoma be considered in the differential when diagnosing adults with right lower quadrant pain.